Promoting collaboration to enhance learning in modern foreign languages - Lougher, E (2016)
This paper details school-based research conducted to gather pupil views on group work and promote collaboration to enhance learning in French lessons at a British junior school. A dual-phase intervention centred on a sample of 74 pupils in Year 5 and saw the collaborative design, implementation and evaluation, by four teachers, of tasks drawing on the cooperative learning principles of positive interdependence, individual accountability, social skills, group processing and promotive interaction. Questionnaires were employed to gather views at different stages of the enquiry, allowing for quantitative analysis; data was also gathered via qualitative techniques such as lesson observations and semi-structured interviews. A majority of pupils claimed to enjoy working together, learning from others and helping one another, with many citing teamwork as a key facilitator to effective collaboration and warning of the negative implications of arguing, bossiness and disruption. The role of the teacher was considered key to the efficacy of group work, with proficient task design and efficient classroom management seen as especially important. Overall, cooperative learning strategies were deemed effective in enhancing the quality of group work in French lessons, this judgment being based primarily on the observations and experiences of the pupils and teachers involved. The key findings from this study have been collated to form a set of guidelines, intended as a point of reference in the future planning and execution of group work in this setting.